Evolutionarily Ancient Caspase-9 Sensitizes Immune Effector Coelomocytes to Cadmium-Induced Cell Death in the Sea Cucumber, Holothuria leucospilota - Li, Xiaomin; Chen, Ting; Wu, Xiaofen; Li, Zhuobo; Zhang, Xin; Jiang, Xiao; Luo, Peng; Hu, Chaoqun; Wong, Nai-Kei; Ren, Chunhua (Frontiers in Immunology, 2022)
Heavy-metal pollution has increasingly jeopardized the habitats of marine organisms including the sea cucumber, a seafloor scavenger vital to seawater bio-decontamination, ocean de-acidification and coral-reef protection. Normal physiology including immune functions of sea cucumbers is toxicologically modulated by marine metal pollutants such as cadmium (Cd). The processes underpinning Cd’s toxic effects on immune systems in the sea cucumber, Holothuria leucospilota, are still poorly understood. To this end, we cloned and characterized a full-length caspase-9 (Hl-CASP9) cDNA in the sea cucumber, Holothuria leucospilota. Hl-CASP9 mRNA levels evolved dynamically during embryonic development. Coelomocytes, a type of phagocytic immune effectors central to H. leucospilota immunity, were found to express Hl-CASP9 mRNA most abundantly. Hl-CASP9 protein structurally resembles caspases-2 and -9 in both invertebrate and vertebrate species, comprising a CARD domain and a CASc domain. Remarkably, Hl-CASP9 was transcriptionally sensitive to abiotic oxidative stress inducers including hydrogen peroxide (H2O2), nitric oxide (•NO) and cadmium (Cd), but insensitive to immunostimulants including lipopolysaccharide (LPS), and poly(I:C). Overexpression of Hl-CASP9 augmented mitochondria-dependent apoptosis in HEK293T cells, while knock-down of Hl-CASP9 blunted Cd-induced coelomocyte apoptosis in vivo. Overall, we illustrate that an evolutionarily ancient caspase-9-dependent pathway exists to sensitize coelomocytes to premature cell death precipitated by heavy metal pollutants, with important implications for negative modulation of organismal immune response in marine invertebrates.